Acculturation and nutritional health of immigrants in Canada: a scoping review - Sanou, Dia; O'Reilly, Erin; Ngnie-Teta, Ismael; Batal, Malek; Mondain, Nathalie; Andrew, Caroline; Newbold, Bruce K; Bourgeault, Ivy L (Université d'Ottawa | University of Ottawa, 2013)
Although recent immigrants to Canada are healthier than Canadian born (i.e., the Healthy Immigrant Effect), they experience a deterioration in their health status which is partly due to transitions in dietary habits. Since pathways to these transitions are under-documented, this scoping review aims to identify knowledge gaps and research priorities related to immigrant nutritional health. A total of 49 articles were retrieved and reviewed using electronic databases and a stakeholder consultation was undertaken to consolidate findings. Overall, research tends to confirm the Healthy Immigrant Effect and suggests that significant knowledge gaps in nutritional health persist, thereby creating a barrier to the advancement of health promotion and the achievement of maximum health equity. Five research priorities were identified including (1) risks and benefits associated with traditional/ethnic foods; (2) access and outreach to immigrants; (3) mechanisms and coping strategies for food security; (4) mechanisms of food choice in immigrant families; and (5) health promotion strategies that work for immigrant populations.
Keywords: Dietary acculturation; Immigrant health; Canada; Nutrition